2003
DOI: 10.1159/000073042
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heterogeneity in Gene Expression Profiles: A Transcript Analysis in Human and Rat Heart

Abstract: Background: Investigations involving biopsies of human cardiac tissue often assume that myocardial samples from a specific location are representative of the entire heart. Hypothesis: There are significant regional differences in gene expression in the heart. Methods: We used two models. In the first model, seven whole human hearts were cut in 1-cm slices from apex to base and 11 distinct regions were sampled. Full thickness left ventricular tissue was further subdivided equally into an inner, outer, and middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…A higher activity of glucose metabolism is associated with a faster contraction related to myosin heavy chain (MyHC) isoform expression. Interestingly, a lower expression of MyHCβ and a higher expression of MyHCα with higher ATPase activity [56,57,58] in the RV as compared to the LV [59,60], indicate that the RV exhibits a faster muscle phenotype. Indeed, the shortening velocity of the RV muscle is greater than that of the LV [59].…”
Section: Discussionmentioning
confidence: 99%
“…A higher activity of glucose metabolism is associated with a faster contraction related to myosin heavy chain (MyHC) isoform expression. Interestingly, a lower expression of MyHCβ and a higher expression of MyHCα with higher ATPase activity [56,57,58] in the RV as compared to the LV [59,60], indicate that the RV exhibits a faster muscle phenotype. Indeed, the shortening velocity of the RV muscle is greater than that of the LV [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators have suggested regional differences in myocardial structure and function, potential regional differences related to glucose metabolism have been infrequently investigated (13,14,29). Because of its hydrophilic nature, glucose is unable to pass the lipid bilayer of the plasma membrane by simple diffusion, thus the rate-limiting step for cardiac glucose utilization is glucose uptake, which is preceded and induced by translocation of GLUTs from an intracellular site to the cell surface (28).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the crucial role of glucose utilization in the heart and regional differences in myocardial structure and function (14,29), the potential regional pattern in the regulation of glucose transport in the healthy myocardium and during chronic HF has not been investigated. Since glucose entry across the sarcolemma is regulated by GLUT, we hypothesized that 1) insulinresponsive GLUT4 and -12 protein expression will be chamber specific in the healthy and in the failing myocardium; 2) GLUT4 and -12 protein and mRNA expression will be altered during chronic HF.…”
mentioning
confidence: 99%
“…We have recently also shown that gene expression of markers of heart failure vary not only transmurally, but also within different regions of the left ventricle. [5] Our study and the study by Baba et al examined myocardial tissue from the apex. It is possible that even within a small anatomical region there are significant differences in protein activity.…”
mentioning
confidence: 72%